DAMPAK GAYA KOGNITIF TERHADAP PEROLEHAN BELAJAR KONSEP STATISTIKA - Rufii, Rufii (WAHANA, 2011)
The purposes of the study were to examine the result of analysis differences in the acquisition of learning concepts of statistics among learners who studied with field independence cognitive styles and field dependence. The results are expected to provide benefits, namely: (1) pay attention to the characteristics of learners such as cognitive styles, (2) to find a process of learning the concept of Statistics. Subjects were fourth semester undergraduate students of academic year 2009/2010, Third Diploma students Midwifery Studies Program PGRI Adi Buana University of Surabaya which consists of two classes of 76 people. Subjects were taken at randomly, and the total member are 94 people. Research hypotheses were tested with non parametric statistical test Mann Whitney. Results showed that there is difference in the acquisition of learning concepts among students who studied statistics with cognitive style of field independence and field dependence (U=450; and probability of 0.012<0,05). Average score of the acquisition of cognitive learning style concept Statistics field independence of 63.97 higher than the cognitive style field dependence of 58.19. Based on the findings of this study suggested the following for researchers interested in the substance of this study, the findings of this study provide inputs for designing the research to be done, and can develop and dig deeper into those aspects related to learning strategies that have not been reached in this study.